2011
DOI: 10.1371/journal.pone.0022806
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the p38 MAPK Signaling Pathway in High Glucose-Induced Epithelial-Mesenchymal Transition of Cultured Human Renal Tubular Epithelial Cells

Abstract: BackgroundEpithelial-mesenchymal transition of tubular epithelial cells, which is characterized by a loss of epithelial cell characteristics and a gain of ECM-producing myofibroblast characteristics, is an essential mechanism that is involved in tubulointerstitial fibrosis, an important component of the renal injury that is associated with diabetic nephropathy. Under diabetic conditions, p38 MAPK activation has been reported in glomeruli and mesangial cells; however, studies on p38 MAPK in TECs are lacking. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
90
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 47 publications
4
90
0
1
Order By: Relevance
“…P38 MAPK (p38) is a member of the MAPK family and is in close association with a variety of renal diseases 20, 21, 22. We found hyper‐activity of p38 was driven by ox‐LDL, compared with the controls ( P < 0.05; Fig.…”
Section: Resultsmentioning
confidence: 76%
“…P38 MAPK (p38) is a member of the MAPK family and is in close association with a variety of renal diseases 20, 21, 22. We found hyper‐activity of p38 was driven by ox‐LDL, compared with the controls ( P < 0.05; Fig.…”
Section: Resultsmentioning
confidence: 76%
“…14) TGF-β 1 and CTGF have been found to be up-regulated in both experimental and human DN, and to be associated with EMT, 7,10,11,[15][16][17][18][19][20][21] supporting a key role for these signaling molecules. A previous study in diabetic rats showed that using fasudil as a treatment also decreased EMT.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] Overaccumulation of ECM in the tubulointerstitium is known to lead to tubulointerstitial fibrosis, and this is thought to be an important contributor to DN pathogenesis. 36) There are emerging evidences that a large proportion of the myofibroblasts that secrete ECM are derived from EMT of tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under basal conditions, Trx in mitochondria binds and inhibits ASK (apoptosis signalregulating kinase)-1, an upstream MKK3/6 and p38 MAPK activator (61)(62)(63). TxNIP up-regulation has been proposed to bind Trx and release ASK-1 to activate p38 (64 -66), which in turn would stimulate AP-1 (67,68). In support of this possibility, TxNIP has recently been reported to translocate to the mitochondria in the presence of ROS in pancreatic ␤-cells (65).…”
Section: Discussionmentioning
confidence: 99%